1987
DOI: 10.1021/bi00379a038
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared studies of proteins using nonaqueous solvents. Effects of methanol and ethylene glycol on albumin and immunoglobulin G

Abstract: An infrared/attenuated total reflection (ATR) technique has been utilized to study the structural changes in proteins induced by nonaqueous solvents, without the need of dissolving the protein in the nonaqueous solvent. For the two proteins studied, methanol and ethylene glycol caused similar changes in albumin, i.e., an increase in helix secondary structure. However, the two solvents had dissimilar effects on immunoglobulin G (IgG). Changes in the pH of aqueous solutions of IgG produced a third effect. By dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
43
1
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 9 publications
7
43
1
1
Order By: Relevance
“…It shows that the deviation in the average of each characteristic frequency is in the worst case Ϯ5 cm Ϫ1 . These positions are in very good agreement with those reported in the literature for IgG using different IR methods (ATR and transmission) and using different mathematical manipulations of the data, such as SD, CF, or Fourier self-deconvolution (7,10,(21)(22)(23).…”
Section: Structural Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…It shows that the deviation in the average of each characteristic frequency is in the worst case Ϯ5 cm Ϫ1 . These positions are in very good agreement with those reported in the literature for IgG using different IR methods (ATR and transmission) and using different mathematical manipulations of the data, such as SD, CF, or Fourier self-deconvolution (7,10,(21)(22)(23).…”
Section: Structural Analysissupporting
confidence: 89%
“…This multiplicity between 1620 and 1640 cm Ϫ1 of "␤-peaks" has been frequently observed in ␤-sheetcontaining proteins and reflects differences in the hydrogen bonding strength, as well as differences in transition dipole coupling in different ␤-strands (12). The high-frequency "␤-component" may overlap with contributions from ␤-turns and unordered structures, and it is not univocally related to a particular absorption peak: in the literature the peaks observed between 1690 and 1660 cm Ϫ1 were assigned to either ␤-turns or ␤-sheet (7,10,21). Based on the spectra of proteins with very high ␤-sheet content, Byler and Susi (7,13) assign the peaks observed in the region 1680 -1670 cm Ϫ1 to the highfrequency component of the ␤-sheet structure and suggested that the sum of all the integrated areas of the "␤-peaks," as a fraction of the total amide I band area, is closely related to the total "␤-content" of a given protein.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because although the FTIR bands in the amide I region directly correspond to these secondary structural elements (16,17), the line broadening in the spectra of lyophilized proteins, combined with strongly overlapping bands, make such quantitation in this region arduous (15,18). Another spectral region, the amide III band (1220-1330 cm-'), also reflects the secondary structure of proteins (19)(20)(21) and has been used to characterize structural changes qualitatively (22)(23)(24)(25)(26) and, in aqueous solution, even to quantify the individual secondary structure composition of proteins (19)(20)(21)27). …”
mentioning
confidence: 99%
“…ATR-FTIR has been shown to be useful for studying the secondary structure and other properties of proteins in a variety of environments (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Two ATR methods have been used for studying soluble proteins.…”
mentioning
confidence: 99%